Assignment And Thesis Writing - Anderson, Jonathan; Poole, Millicent (New Delhi: Wiley, 2019)
This book is a standard reference to assist students in all aspects of writing assignments, reports, term papers, projects, dissertations or theses.This edition has been thoroughly updated to reflect the impact of information technology on writing and research. New sections have been included on citing and referencing a range of electronic information sources, using search engines effectively, and errors to avoid in your writing.
Keywords: Assignment--Thesis Writing